Following the steps of CHIPA: Chilenia and Patagonia formed the same drift terrain that collided with the southwest Gondwana margin during the middle Paleozoic - Tomezzoli, Renata Nela; Cristallini, Ernesto O.; Tickyj, Hugo; Arzadún, Guadalupe; Calvagno, Juan Martín; Choque, Giselle; Febbo, Belen; Saguas, Eliana (Frontiers in Earth Science, 2023)
Geological evidence indicates that the deformation along the southwest Gondwana margin began during the middle to Late Devonian (Acadian - Cháñica orogenic phase in Argentina). Here it is interpreted that is consequence of the collision of Chilenia from the west and Patagonia from the south-southwest against Gondwana. Since both Chilenia and Patagonia collided at the same time, in this work we proposed that these continental blocks conform the same allochthonous drift terrain, here named as CHIPA. The geological evolution of this margin is still under debate. Field works, paleomagnetic and anisotropy of magnetic susceptibility (AMS) studies, were integrated from different localities along this paleo-margin in Argentina. While in rocks of Permian age, all the geological indicators show a clear regional NW-SE elongation signature and NE-SW shortening direction, the older Middle Devonian to the Permian ages patterns are more complex, as the result of stress interference and overlapping of orogenic activities with different intensities and ages. The deformation that started as the product of the CHIPA collision against Gondwana during the Middle Devonian, continued up to the Permian (Hercinian-San Rafael orogenic phase in Argentina) as post-collisional compressive deformation, consequence of the paleogeographic re-organization of Gondwana and Laurentia that moved towards the Equator from the south and the north respectively, to form the Pangea supercontinent during the Triassic.